Work Characteristics and Occupational Well-Being: The Role of Age - Zacher, Hannes; Schmitt, Antje (Frontiers in Psychology, 2016)
Based on a lifespan perspective on work design, person-environment interaction and fit theories, models of successful aging at work, and role theory, we review research on the role of worker age in relationships between work characteristics and occupational well-being. We first focus on interaction effects of work characteristics and age on occupational well-being. Research has found that age can moderate associations between work characteristics and occupational well-being indicators, and that work characteristics can moderate associations between age and occupational well-being indicators. Next, we describe research showing that work characteristics can mediate associations between age and occupational well-being indicators. The relationships of age with specific work characteristics and occupational well-being indicators can be linear or non-linear. We conclude our literature review by discussing implications for future research.